2020
DOI: 10.1111/jphp.13242
|View full text |Cite
|
Sign up to set email alerts
|

Urinary metabolomics research for Huangqi Jianzhong Tang against chronic atrophic gastritis rats based on 1H NMR and UPLC-Q/TOF MS

Abstract: Objectives As a traditional Chinese medicine (TCM), Huangqi Jianzhong Tang (HQJZ) has a good efficacy in treating chronic atrophic gastritis (CAG). Our objective was to determine its mechanism based on the urine comprehensive metabolome. Methods In the study, a metabolomic approach was applied to reveal the efficacy of HQJZ on the constructed CAG rats coupled with proton nuclear magnetic resonance (1H NMR) and ultra‐performance liquid chromatography/quadrupole time‐of‐flight mass spectrometry (UPLC‐Q/TOF MS). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…Folate, as a vitamin, is able to improve gastric mucosal damage and teprenone is a gastric mucosal protective agent (34,35). In the present study, the positive control drugs selected for the rat model of CAG were folate and teprenone, as these have a certain effect to improve gastric atrophy according to previous experimental results (23,25). Furthermore, the positive control drugs inhibited the expression levels of Wnt signal-related genes.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Folate, as a vitamin, is able to improve gastric mucosal damage and teprenone is a gastric mucosal protective agent (34,35). In the present study, the positive control drugs selected for the rat model of CAG were folate and teprenone, as these have a certain effect to improve gastric atrophy according to previous experimental results (23,25). Furthermore, the positive control drugs inhibited the expression levels of Wnt signal-related genes.…”
Section: Discussionmentioning
confidence: 67%
“…In recent years, significant progress has been made in the treatment of patients with CAG using TCM (20,21). Previous in vivo studies have indicated that TCM formulations are able to improve gastric mucosal atrophy, including Modified Sijunzi Decoction (22), Weiqi Decoction (23), Banxia Xiexin Decoction (24) and Huangqi Jianzhong Tang (25). Jianpiyiqi formula is a TCM prescription that may be used to effectively treat CAG in the clinic (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…[10] found that both electroacupuncture and moxibustion could restore various caG-induced metabolic changes, including membrane metabolism, energy metabolism and neurotransmitter function. Liu Yuetao [11] based on 1 H-NMR technical analysis astragalus chienchung soup to the CAG rats serum endogenous metabolites regulation function disorder, through multivariate statistical analysis, to clarify its regulation on chronic atrophic gastritis targets, related indicators associated with efficacy is established, by partial least-squares regression analysis and Met PA screening and treatment effect is most related metabolic pathways, find the root of remembranous milk vetch chienchung soup can obviously inhibit the CAG lesions, can obviously regulate 3hydroxy butyric acid lactic acid acetate succinate metabolites such as disorder, the CAG treatment is the main metabolic pathways of arginine-proline metabolismGlycerol metabolism and glycine-serine-threonine metabolism pathways. Sun Yina [12] found 59 qualitative and quantitative metabolites, and then PCA OPLS-DA VIP value was used to find 8 potential differential metabolites related to dampis-heat syndrome of spleen and stomach.…”
Section: Discussionmentioning
confidence: 99%
“…Vitacoenzyme (VTE) tablets have been clinically used to treat CAG due to their good curative effects (Liu et al, 2018; Liu et al, 2020); thus, VTE was selected as the positive drug in this study. After 7 days of acclimatization, 50 rats were randomly divided into five groups (10 rats in each group): control group, model group, VTE‐positive group (0.3 g/kg), low‐dose SDG group (14.04 g crude herbs per kg), and high‐dose SDG group (28.08 g crude herbs per kg).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, traditional Chinese medicine (TCM) prescriptions, which have remarkable therapeutic effects with fewer side effects, have been widely used to treat CAG in clinics, (Liu et al, 2020; Xu et al, 2020). Among these TCM prescriptions, Shidan granules (SDG) have drawn extensive attention because of their excellent curative effects on CAG.…”
Section: Introductionmentioning
confidence: 99%